Application of the Law to Perpetrators of Criminal Acts of Abortion and Owners of Illegal Abortion Practices (Study Decision Number 286/Pid.Sus/2021/Pn Jkt.Tim) - Muhammad Fadlan; Risdalina Risdalina; Maya Jannah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This research uses normative legal research methods to examine the application of criminal sanctions against abortion perpetrators and owners of illegal abortion practices based on Decision Number 286/Pid.Sus/2021/PN Jkt.Tim. In this decision, the judge sentenced the defendant to imprisonment for 2 years and 6 months and a fine of Rp. 50,000,000.00, with the provision that if it was not paid, it would be replaced by imprisonment for 3 months. This decision was deemed appropriate because the defendant was legally and convincingly proven to have practiced illegal abortion together, violating Article 75 paragraph (1) in conjunction with Article 194 of Law no. 36 of 2009 concerning Health and Article 55 paragraph (1) 1 of the Criminal Code. The aggravating circumstance is that the defendant's actions are contrary to human values ​​and endanger the safety of other people. Meanwhile, mitigating circumstances are that the defendant behaved politely at trial, had never been convicted, and admitted his actions honestly and regretted them. The driving factor for the abortion was pressure from the work contract which caused witness R and witness NAS to be forced to have an abortion because they were worried about losing their jobs. Apart from that, illegal abortion practices are carried out for economic gain, where patients have to pay around IDR 8.5 million to have an abortion. This reflects weak supervision of illegal health practices and low awareness of the health dangers they cause